Frequency of depression, anxiety and stress in patients with acne vulgaris - Rafiq, Zahid; Mehdi, Syed Muntazir (Journal of Pakistan Association of Dermatologists, 2021)
Objective To determine the frequency of depression, anxiety and stress among acne vulgaris patients. Â Methods This cross-sectional study was conducted in Department of Dermatology at DHQ/ GHAQ Teaching Hospital/ Sahiwal Medical College, Sahiwal after approval from ethical review committee. A total of 100 patients of acne vulgaris filling the inclusion and exclusion criteria were enrolled. Acne severity was graded into three grades mild, moderate and severe. DASS (Depression Anxiety Stress Score) questionnaire (21 Questions) was translated and filled on proforma. Data was analyzed by SPSS. Â Results In 100 patients, there were 58 females and 42 males. Mean age was 21 years in both genders. There was significant number of patients (39%) with family history of acne vulgaris. Majority of them were students (59%) and unmarried (82%).Â Mild (47%) and moderate (43%) severity of acne vulgaris constitute 90% of total patients and rest of patients (10%) belonged to severe form. Depression was observed in most cases (62%) as compared to anxiety (51%) and stress (40%) in different severity of acne patients. Moderate degree of depression 48% (n=30) and anxiety 49% (n=25) cases and mild degree of stress 50% (n=20) cases were noticed in majority among different severity of acne vulgaris. Â Conclusion There is significant impact of psychological issues on acne vulgaris patient as shown by frequency of depression, anxiety and stress in this study. Thus, highlight the need of close liaison of dermatologist and psychiatrist in management of acne vulgaris. Â